DISTRIBUTION PATTERNS AND AREAS OF ENDEMISM OF BRAZILIAN JACQUEMONTIA (CONVOLVULACEAE) SPECIES - Buril, M. T.; Maciel, J. R.; Alves, M. (Edinburgh Journal of Botany, 2014)
This study aims to understand the distribution of species of Jacquemontia (Convolvulaceae) in Brazil and to determine the centre of endemism of the genus in that country. A database of around 2000 records of samples deposited in 46 herbaria was created. Twenty-one species were classified as widely distributed, of which 14 have continuous distributions and seven have disjunct ones. The remaining 26 species were classified as restricted and among these, 14 were considered endemic and 12 microendemic. The centre of endemism of the genus is in the Espinhaço Range, which traverses Bahia and Minas Gerais. The distribution patterns are discussed and a new assessment for the Red List of Jacquemontia is suggested.
Keywords: Caatinga; Cerrado; Dry Forests; Espinhaço Range; Pleistocene Arc